Impact of cadmium on photosynthetic pigments, root structure, and nutrient concentrations in bean (Phaseolus vulgaris L.) plants - Gutiérrez-Martínez, Paulina Beatriz (2024)
Cadmium (Cd) is a contaminant that causes significant damage to organisms. In plants, it results in growth delay, alters photosynthetic function, and affects nutrient concentrations. This study aimed to evaluate the impact of Cd (0, 0,25, 0,50, and 1 µM) on chlorophyll content, structural damage to the root, and the absorption and translocation of nutrients (Ca, K, Mg, Mn, Fe, and Zn) in Phaseolus vulgaris var. Opus plants. An increase in chlorophyll a was observed at Cd concentrations of 0.25 and 1 µM. Chlorophyll b increased across all Cd treatments, while carotenoid content decreased in all treatments. The roots exhibited structural damage as Cd concentrations increased. For nutrients, Ca, Mg, Mn, and Zn in leaves, and K in stems, increased with higher Cd doses. Conversely, K in roots decreased with higher Cd concentrations, and Fe decreased compared to the control in all evaluated organs. Our results suggest that Cd stress at low concentrations stimulates chlorophyll synthesis and that varying Cd concentrations induce synergistic and antagonistic effects in different organs of P. vulgaris, leading to nutritional disorders. Given the global importance of this crop, studying the molecular mechanisms and membrane transporters in P. vulgaris roots exposed to Cd is crucial for enhancing its resistance to Cd.